Pedotransfer functions of potentially toxic elements in tropical soils cultivated with vegetable crops - Boim, Alexys G. F. (2020)
The anthropogenic input of potentially toxic elements (PTEs) from industry, agrochemicals, etc., into the environment are of great concern. Models derived from pedotransfer functions can provide estimates of the levels of PTEs based on soil attributes. Based on the importance of these models in studies in contaminated areas, we assessed the concentrations of the reactive contents of Ba, Cu, Cr, Ni, Pb, and Zn in soils cultivated with vegetable crops in the state of São Paulo, Brazil. We also evaluated the influence of chemical and physical soil attributes on their reactivity and availability. The reactive contents of PTEs represent the fraction of PTEs easily sorbed at the adsorptions sites of organic matter, iron hydroxides, or clay. This fraction can supply information about the PTE content that is more or less readily released into the soil solution. The reactive and available fraction was extracted with 0.43 M HNO3 and 0.01 M CaCl2, respectively. The proportion of reactivity of metal pools decreased in the order of Ba>Zn > Cu > Pb > Ni > Cr. The empirical models were able to predict the relationship between the reactive fractions, the pseudototal content, and the soil attributes. The available concentrations of Cr, Cu, Ni, and Pb in the soils were lower than the limit of quantification, while 3% of the Ba content and 1% of the Zn content were available in the soil solution in relation to their pseudototal content, suggesting low mobility of these elements in the soil.